2001
DOI: 10.1177/152660280100800312
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stent-Grafting in the Treatment of Superficial Femoral Artery Occlusive Disease

Abstract: Intraoperative use of the Hemobahn endograft is feasible and effective in restoring adequate distal perfusion in the short term, especially when combined with conventional recanalization techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…1 For the management of femoralepopliteal atherosclerotic disease with a suitable above-the-knee (AK) popliteal landing zone, multiple studies have now demonstrated that polytetrafluoroethylene (PTFE)-covered stent-grafts offer good short-and long-term primary and secondary patency rates. [2][3][4][5][6][7][8][9][10][11] Patency rates of PTFE stent-grafts in these studies are equivalent to those found in analyses of femoralepopliteal bypass surgery using conventional PTFE grafts. [12][13][14][15] A prospective, randomized controlled trial comparing PTFE stent-grafts and PTFE bypass grafts demonstrated equivalent patency at 1 and 2 years.…”
supporting
confidence: 56%
“…1 For the management of femoralepopliteal atherosclerotic disease with a suitable above-the-knee (AK) popliteal landing zone, multiple studies have now demonstrated that polytetrafluoroethylene (PTFE)-covered stent-grafts offer good short-and long-term primary and secondary patency rates. [2][3][4][5][6][7][8][9][10][11] Patency rates of PTFE stent-grafts in these studies are equivalent to those found in analyses of femoralepopliteal bypass surgery using conventional PTFE grafts. [12][13][14][15] A prospective, randomized controlled trial comparing PTFE stent-grafts and PTFE bypass grafts demonstrated equivalent patency at 1 and 2 years.…”
supporting
confidence: 56%
“…L'occlusione cronica dell'arteria femorale superficiale (AFS) è causa di claudicatio e può condurre all'instaurarsi di uno stato di ischemia cronica critica [1]. In considerazione degli elevati tassi di morbidità e mortalità correlati a questa patologia, sono state proposte differenti opzioni terapeutiche, rappresentate dagli interventi chirurgici di by-pass femoro-popliteo, dalle tecniche combinate di tromboendoarteriectomia mediante anelli di Wollmar associate o meno allo stenting [2,3] e dalla rivascolarizzazione percutanea. Quest'ultima, grazie anche ai vantaggi della minore invasività e morbilità, ha ampliato le proprie indicazioni: infatti, mentre in passato venivano sottoposte a questa procedura solo steno-occlusioni brevi, attualmente sono suscettibili di trattamento anche lesioni ostruttive più estese in lunghezza [4].…”
Section: Methodsunclassified
“…Chronic occlusion of the superficial femoral artery (SFA) causes claudication and may lead to chronic critical limb ischaemia [1]. In view of the high morbidity and mortality of peripheral arterial disease, different treatment options have been proposed, including femoropopliteal bypass surgery, combined thromboendarterectomy techniques using Wollmar ring strippers with optional stenting [2,3] and percutaneous revascularisation. The indications for this last option have been extended in part as a result of its less invasiveness and lower morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…93% in der femoralen Achse [11]. Diese Ergebnisse konnten jedoch von anderen Gruppen bei der A.femoropoplitea nur selten oder allenfalls bei "Idealindikationen" reproduziert werden [1,2,6,7,10]. Deutschmann et al berichteten gar über völlig unbefriedigende Offenheitsraten trotz exzellenter initialer angiographischer Ergebnisse, die sie u. a. auf die Entwicklung intimaler Hyperplasien an den Stentgraftenden zurückführten [6].…”
Section: Interventionelle Behandlung Von Stenosen Und Verschlüssen Deunclassified